Peer Counselor as A Preventive Effort Against Early Marriage Using the Health Belief Model Approach - Damayanti, Eka; Astuti, Dhesi Ari (Buletin Ilmu Kebidanan dan Keperawatan, 2024)
Early-age marriage presents a significant challenge in many developing countries, including Indonesia. Marriages occurring before the age of 18 often lead to adverse outcomes for adolescents, including pregnancy and childbirth complications that elevate maternal and infant mortality rates. Additionally, early marriage commonly disrupts adolescent education, limiting future employment opportunities. Effective preventive strategies, such as the "KOTESA" initiative, empower adolescents using the Health Belief Model (HBM) approach. This study employed qualitative methods with a descriptive phenomenological approach, gathering data through in-depth interviews. Most participants were adolescents married before age 16, many experiencing their first pregnancy at a similarly young age. Such early marriages impact adolescents’ health, education, and economic prospects. Intervention through peer counseling, guided by the HBM approach, proved effective in increasing adolescent knowledge about reproductive health and in serving as a preventive measure against early marriage. The KOTESA program involves adolescents as peer counselors utilizing the Health Belief Model framework, which emphasizes behavioral change by enhancing perceptions of risk, highlighting benefits, and reducing barriers to prevent early marriage. It is recommended that stakeholders promote and support the KOTESA peer counseling model to encourage behavioral change among adolescents and reduce early marriage rates.